FAKTOR-FAKTOR YANG BERHUBUNGAN ANTARA IBU HAMIL DENGAN KUNJUNGAN ANC K1 DI PUSKESMAS LIMA ILIR TAHUN 2023: FAKTOR-FAKTOR YANG BERHUBUNGAN ANTARA IBU HAMIL DENGAN KUNJUNGAN ANC K1 DI PUSKESMAS LIMA ILIR TAHUN 2023 - Dessi Irmala Sari; Wiwit Wulandari (Politeknik Kesehatan Kemenkes Bandung, 2025)
According to the World Health Organization (2013), approximately 15% of pregnant women experience complications that can endanger their lives, often due to a lack of understanding about bodily changes during pregnancy. This study aimed to examine factors associated with ANC K1 visits among pregnant women at the Lima Ilir Health Center in 2023. An accidental sampling method was applied, involving all pregnant women who underwent ANC K1 examinations at the Lima Ilir Health Center from November to December 2023, with a total sample of 30 respondents. Data were analyzed using univariate and bivariate methods. The findings revealed that 21 participants (70%) attended ANC K1 visits, while 9 participants (30%) did not. Chi-Square test results at a significance level of α = 0.05 indicated no significant association between mothers’ knowledge (p = 0.815) and parity (p = 0.09) with ANC K1 visits, but a significant relationship was found between educational level and ANC K1 attendance (p = 0.016). It is recommended that the Lima Ilir Health Center enhance health education programs to emphasize the importance of ANC K1 visits in monitoring both maternal and fetal health.